مكانة القياسات و الإختبارات في تقويم الصفات البدنية لدى لاعبي كرة القدم للفئات الشبانية - زبالح, عدة; زايدي, يوسف (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
هدف البحث إلى الكشف عن مكانة الاختبار والقياسات في تقويم الصفات البدنية لدى اللاعبين الناشئين في كرة القدم، تم الاعتماد في هذا البحث على المنهج الوصفي حيث اعتمد الطالبان على إعداد استمارة استبيانيها كأداة للبحث، وتكونت عينة البحث من 24 مدربا لبعض الفرق للفئات الشابة لولاية غليزان تم اختيارهم بطريقة عشوائية وبعد القيام بالدراسة الإحصائية توصل الطالبان إلى ثبوت صحة فرضيات الدراسة التي نصت على أن أهمية الاختبارت والقياسات في تقويم الصفات البدنية لدى لاعبي كرة القدم للفئات الشابة، و في الأخير يوصي بضرورة تكوين المدربين في مجال الاختبار والقياس، وتوفير الوسائل التكنولوجية الحديثة. // // // // // Abstract The objective of the research is to reveal the place of tests and measurements in the evaluation of the physical characteristics of young football players. In this research, the descriptive approach was privileged, the two students having relied on the preparation of a questionnaire as a research tool. The research sample consisted of 24 coaches for selected teams for youth groups in Relizane State. By choosing them at random, and after carrying out the statistical study, the two students concluded that the hypotheses of the study proved to be correct, which stipulated that the importance of tests and measurements in the evaluation of the characteristics physics of football players for young groups, and finally recommends the need to train coaches in the field of tests and measurements, and to provide modern technological means.
MES-2024-1
Keywords: الاختبارات والقياسات.- الصفات البدنية. - كرة القدم // // // Tests and measurements - physical parameters - Football